Analisis Pengaruh Pendidikan Dan Kontribusi Sektor Pertanian Terhadap Pertumbuhan Ekonomi Serta Jumlah Penduduk Miskin Di Provinsi Bali Tahun 2004-2013 - Purnami, Ni Made Sasih; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The purpose of this study was to determine the direct and indirect effects of education and agricultural sector contribution to poverty through economic growth in the province of Bali. This research was conducted in all districts / municipalities in Bali Province. Data collected through the documents contained in the BPS Bali. The type of data in this research is secondary data from the years 2004-2013. The analysis technique used is path analysis. The analysis showed the education and agriculture sector contributes directly positive effect on economic growth. Education and economic growth is a direct negative effect on the number of poor people but the contribution of the agricultural sector has a direct positive effect on the number of poor people. Economic growth is a variable that mediates educational variables and variable contribution of the agricultural sector to the number of poor people. The coefficient of determination total is 75.2 percent is explained by the model and the remaining 24.8 percent is explained by other variables outside the model.
Keywords: education; contribution of the agricultural sector; economic growth; poverty